Impact of drying temperatures on drying behaviours, energy consumption and quality of purple sweet potato flour [pdf] - Nguyen Minh Thuy; Le Huy Hiep; Ngo Van Tai; Huynh Thi Thu Huong; Vo Quang Minh (My University, 2022)
Sweet potato (Ipomoea batatas L.) is an important crop providing food for humans and raw materials for industrial processing plants to create high economy products.According to the restructuring of the agriculture sector in Vinh Long province, each year there is an attempt to stabilize the sweet potato growing area from 10,500 to 11,000 hectares, with an output of 300,000-400,000 tons, which is home to a large sweet potato
Keywords: Food Drying and Modeling